2023
DOI: 10.3389/fimmu.2023.1099017
|View full text |Cite
|
Sign up to set email alerts
|

Substance P aggravates ligature-induced periodontitis in mice

Abstract: Periodontitis is one of the most common oral diseases in humans, affecting over 40% of adult Americans. Pain-sensing nerves, or nociceptors, sense local environmental changes and often contain neuropeptides. Recent studies have suggested that nociceptors magnify host response and regulate bone loss in the periodontium. A subset of nociceptors projected to periodontium contains neuropeptides, such as calcitonin gene-related peptide (CGRP) or substance P (SP). However, the specific roles of neuropeptides from no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Retrograde labeling by injecting a tracer into mouse gingiva has demonstrated that periodontal afferents are primarily small- and medium-diameter neurons ( 46 , 72 ). Among these, 23% are CGRP-positive and 28% are TRPV1-positive.…”
Section: Primary Afferent Contributions To Orthodontic Painmentioning
confidence: 99%
See 4 more Smart Citations
“…Retrograde labeling by injecting a tracer into mouse gingiva has demonstrated that periodontal afferents are primarily small- and medium-diameter neurons ( 46 , 72 ). Among these, 23% are CGRP-positive and 28% are TRPV1-positive.…”
Section: Primary Afferent Contributions To Orthodontic Painmentioning
confidence: 99%
“…TRPV1-expressing nociceptors can also contribute to the development of orthodontic pain. As TRPV1 and neuropeptides are highly colocalized in periodontal afferents ( 46 , 72 ), and nerve terminals containing neuropeptides such as CGRP and substance P (SP) are projected into periodontal ligaments ( 77 , 78 ), the activation of TRPV1-expressing nerve terminals by orthodontic forces can induce the release of neuropeptides such as CGRP or SP into the periodontal tissues. These neuropeptides play crucial roles in vasodilation and the recruitment of immune cells to damaged tissue ( 79 ).…”
Section: Primary Afferent Contributions To Orthodontic Painmentioning
confidence: 99%
See 3 more Smart Citations